DAMPAK PEMBERIAN EKSTRAK BIJI HIJAU KOPIARABIKA (Coffea Arabica L) ACEH GAYO TERHADAP KADAR GLUKOSA DARAH PUASA PADA MENCIT (Musmusculus L) JANTAN GALUR SWISS-WEBSTER MODEL DIABETES MELITUS - Afrizaldi Pramadana Handoko (2019)
Diabetes melitus is a group of metabolic disease with a characteristic of hyperglicemia. Hyperglycemia can cause multiorgan complication. Flavonoid and chlorogenate acid on arabica coffee beans has an antihyperglycemic effect. The aim of this study was to know the effect of Aceh Gayo green coffee beans extract on fasting blood glucose on Diabetes melitus model Swiss-webster Mice. This study used experimental with pre and post design. Total sample was 25 male mice strain Swiss-webster was induced with alloxan intraperitonally, and treated for 4 weeks. Based on group, (K) standard feed and CMC-Na (normal control), (KP) high fat feed and metformin (positive control), (KN) high fat feed and CMC-Na (negative control), (P1) 0.02g coffee extract 0.39ml/day, and (P2) 0.04g coffee extract 0.78ml/day. Fasting Blood Glucose level was measured through tail lateralis vein using spectrofotometri. Paired T Test result showed existing effect of Aceh Gayo green cofee beans water extract to decrease FGB level on hyperglycemi mice (p<0,05). One Way Anova test followed by Games-Howell post hoc test showed P1 and P2 presented a glycemic control effect can reduce FBG levels, greather than those in KP group. The FBG level decreased on P2 group presented as the lowest mean FBG level, making it the most effective dose in decreasing the FBG level on mice strain Swiss-webster